Analysis of Criminal ACTS That Obstruct the Rights of Citizens Who Express Opinions Reviewed From Law Number 9 of 1998 - Apriyansha Putra Ali (SEAN Institute, 2025)
This study analyzes criminal acts that hinder the right of citizens to express their opinions in public, with a focus on the application of Law Number 9 of 1998 concerning Freedom of Expression of Opinions in Public. Freedom of opinion is a human right guaranteed by the constitution and regulated in Article 28E of the 1945 Constitution and Law No. 9 of 1998. However, the practice often faces challenges in the form of violence, threats, or intimidation from certain parties, including law enforcement officials. This research aims to identify forms of violations, law enforcement mechanisms, and solutions to prevent further violations. The methodology used is a normative juridical approach with an analysis of relevant laws and regulations, such as Article 18 of Law No. 9 of 1998 which provides a maximum of one year of criminal threat for perpetrators of obstruction of freedom of opinion, as well as case studies from empirical data collected by YLBHI and other institutions. The results of the study show that violations of freedom of expression occur in various forms, such as restrictions on demonstrations, criminalization through the ITE Law, and digital attacks on activists. Law enforcement for these violations is often inconsistent and tends to be repressive. The conclusion of this study emphasizes the importance of firm and consistent law enforcement to protect the rights of citizens in expressing their opinions. In addition, collaboration between law enforcement officials and the community is needed to create an environment conducive to freedom of expression without threats or violence. Revisions to regulations such as the ITE Law are also needed to avoid multiple interpretations and abuse of the law. This research makes an important contribution in understanding the challenges of freedom of expression implementation in Indonesia and offers policy recommendations to ensure the protection of human rights.